Covid-19 Containment Strategies: A Comparative Analysis of Hong Kong and Nepal - Rana, Tika; Chalise, Hom Nath (Journal of Karnali Academy of Health Sciences, 2021)
The new type of corona virus officially named as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-2 CoV-2) was first reported in Wuhan China in late December 2019. This article aimed at presenting the preventive strategies implemented against COVID-19 by thegovernment of Nepal and the government of Hong Kong and show how the effective policy discourses coupled with careful preventive measures play critical roles in controlling the virus. This discussion paper is based on various print and non-print media that cover the information about the COVID-19 and the adopted strategies to contain the COVID-19 outbreak in Hong Kong and Nepal. it appears that efficient political leadership, notwithstanding democratically elected or not, people’s health literacy, and effective strategies of the government play key roles in containing the contagion. Government in jurisdictions like Nepal should invest more resources for development of the skilled manpower and conduct more research studies related to the infection prevention and control to deal with the emergency outbreak in the future.